DEVELOPMENT OF THE INSTITUTIONAL SUPPORT MECHANISM FOR SUSTAINABLE REGIONAL DEVELOPMENT - HURIEV, Vladyslav; VASYLIEV, Oleksii; UVAROV, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article addresses the current aspects of sustainable regional development in the context of modern global challenges, such as climate change, depletion of natural resources, social inequality, and political instability. The study presents an analysis of the institutional foundations of sustainable development, which include the legal framework, institutional structures, financial mechanisms, local governance mechanisms, as well as monitoring and evaluation systems. The necessity of creating an effective institutional framework to regulate, coordinate, and support regional development in the long term is substantiated. The evolution of the sustainable development concept is outlined, starting from the first international environmental agreements to modern global initiatives, such as the United Nations Sustainable Development Goals. The main problems of sustainable regional development, including socio-economic inequality, environmental threats, and political barriers, are identified. The study has revealed new opportunities for the development of institutional foundations for sustainable regional development, particularly through decentralization, strengthening the role of local authorities, digitization, and the implementation of innovative management approaches. A mechanism for institutional support of sustainable regional development is proposed, encompassing economic, social, environmental, and infrastructural components. The functions of the mechanism include regulation, coordination, information support, planning, control, mobilization, and the implementation of innovations. This mechanism is aimed at creating conditions for the long-term prosperity of regions, ensuring fair access to resources and opportunities for all population groups. The proposed mechanism is flexible, adaptive to new challenges, and capable of ensuring harmonious regional development in accordance with the needs of future generations.
Keywords: development; sustainable regional development; institutional support mechanism; institutional foundations of sustainable development; institutional support mechanism for sustainable regional development